2007
DOI: 10.1002/cbdv.200790062
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic Recombination of RNA: Possible Mechanism for the Formation of Novel Sequences

Abstract: We report on the formation of novel RNA molecules in a recombination-like, nonenzymatic reaction proceeding in the complex of partially complementary RNA-oligonucleotides under very simple conditions. Analysis of the isolated products demonstrated that at least 5% of the formed linkages are of the (natural) 3',5'-phosphodiester type. We suggest that similar reactions could contribute to the development of the 'RNA world', but could also proceed in vivo within variously structured RNA or RNA complexes containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 19 publications
7
45
1
Order By: Relevance
“…Molecular Dynamics studies, focusing on the area surrounding the ligation site, have indicated multiple opportunities for recombination between model RNAs. Our results also suggest a preference in product formation, which reflects the experimental findings of Lutay et al (2007).…”
supporting
confidence: 87%
“…Molecular Dynamics studies, focusing on the area surrounding the ligation site, have indicated multiple opportunities for recombination between model RNAs. Our results also suggest a preference in product formation, which reflects the experimental findings of Lutay et al (2007).…”
supporting
confidence: 87%
“…The emergence of longer RNA strings could have proceeded not only via polymerization but also through spontaneous rearrangements of RNA sequences that may progress in the absence of any enzymes or ribozymes [351][352][353]; such rearrangements may have dramatically accelerated evolution [57,354].…”
Section: First Settlers In the Zns Worldmentioning
confidence: 99%
“…Pioneering reports of RNA recombination have appeared [7][8][9][10][11][12]. With the possible exception of the systems described in [13][14][15], the reactions reported so far are not simple and robust enough to be of likely prebiotic relevance.…”
Section: Introductionmentioning
confidence: 99%